Redesain Environmental Graphic Design Sign System Candi Pari - Masrafi; Sonhaji Arif (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2021)
The Pari Temple Cultural Heritage is one of the historical sites, relics of the Majapahit kingdom which was victorious in its time. Pari Temple is a cultural heritage that has a fairly intact form with the condition of the temple legs and temple body being quite complete. Observations made by researchers into Pari Temple have found regulations made by the East Java Cultural Heritage Preservation Center (BPCB) which only contain writing without any pictures so that visitors keep making mistakes. Researchers found a solution to protect the temple by implementing environmental graphic regulations in the form of Environmental Graphic Design which was realized into a sign system and wayfinding. The design design method is a solution in developing and creating regulations that function to preserve Pari Temple through a sign system and wayfinding made in the form of an information board that is applied to two-dimensional media that will be placed in the Pari Temple tourist area. The design of the sign system and wayfinding information board is made as good as possible by adding a gupolo statue icon at every point of the regulation. The results of the sign system and wayfinding made can provide behavioral limits to all visitors to Pari Temple so that environmental conditions are maintained properly. The behavioral restrictions made are expected to have good enough results so that the sustainability process that is indirectly carried out by visitors can be carried out. The essence of providing a sign system and wayfinding is the achievement of a media with graphic concepts that exist in the Pari Temple environment can make it easier for visitors to carry out activities, find collectibles and maintain the behavior of every Pari Temple visitor.